Formy i ewolucja integracji w zarządzaniu łańcuchem dostaw - Pokusa, Tadeusz (Forms and the Evolution of Integration in Delivery Chain Management, 2006)
Modern delivery chain is a fast and flexible system related to and directed by customer choice mechanism which aims at meeting the biggest customer satisfaction and, at profits of enterprises creating that chain. Hence, the main task of co-operation among different parts of a delivery chain are both, reaching, due to integration and co-ordination of effectiveness of given enterprises and their chains in whole, and added value operation researches done by all chain parts up to the expected by customers products. The point of the idea, which has been developing since 1980' of XX century and based on co-operation of enterprises in a delivery chain, is making the decisions and actions which are taken to integrate and co-ordinate the processes of the product flow, information, and financial measures from raw materials places to the consumption ones. Additionally, in the new conditions of competition appears the necessity of paying an utmost attention to high quality service, which requires the synchronization of the demand and delivery management. The decisions made and the actions done by all delivery chains begin at the very first stage of product creation and demand planning, and end at the realization of customer order and service one. All the decisions and actions mentioned concern different areas; mainly logistics, marketing, information, research and development works, and finally, the production management. The given article deals with just having been characterized issue, in reference to the form and evolution of integration in the delivery chain management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 323-331